Brachial Pulse Pressure and Cardiovascular or All‐Cause Mortality in the General Population: A Meta‐Analysis of Prospective Observational Studies. Issue 9 (23rd July 2014) - Zhao, Leilei; Song, Yijuan; Dong, Pingshuan; Li, Zhijuan; Yang, Xuming; Wang, Shaoxin
<x xml:space="preserve">Abstract</x> This study aimed to quantitatively evaluate the predictive value of brachial pulse pressure and cardiovascular or all‐cause mortality in the general population based on prospective observational studies by conducting a meta‐analysis. Only prospective observational studies investigating baseline brachial pulse pressure and cardiovascular or all‐cause mortality risk were selected from PubMed and Embase databases until July 2013. Fourteen studies involving 510, 456 participants were analyzed. Pooled risk ratio (RR) of cardiovascular and all‐cause mortality for the highest vs lowest brachial pulse pressure category was 1.80 (95% confidence interval [CI], 1.49–2.17) and 1.32 (95% CI, 1.23–1.41), respectively. Pooled RR of cardiovascular and all‐cause mortality per 10 mm Hg pulse pressure increment was 1.13 (95% CI, 1.10–1.17) and 1.09 (95% CI, 1.07–1.11), respectively. Wide brachial pulse pressure is associated with greater risk of cardiovascular and all‐cause mortality. However, more well‐designed studies specifically on age and sex are needed to further confirm these findings.